2018
DOI: 10.1177/1074840718809710
|View full text |Cite
|
Sign up to set email alerts
|

Struggling and Overcoming Daily Life Barriers Among Children With Congenital Heart Disease and Their Parents in the West Bank, Palestine

Abstract: To my father Shab'an and my mother Jamila Children living with type 1 diabetes and congenital heart disease in the West Bank, Palestine Self-perceived health status, sense of coherence, and the daily life experiences of these children and their parents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 150 publications
1
10
0
Order By: Relevance
“…Religion has been found to facilitate the management of congenital heart disease among adolescents and their parents from Palestine, who stated that illness is God’s will and that, as a consequence, it should be tolerated, rather than objected; religious activities were, thus, intended as a means to receive help, hope, and healing [ 49 ]. Pediatric patients with HIV also endorsed feeling God’s presence and being part of a larger force to a greater extent than their HIV-negative counterparts [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Religion has been found to facilitate the management of congenital heart disease among adolescents and their parents from Palestine, who stated that illness is God’s will and that, as a consequence, it should be tolerated, rather than objected; religious activities were, thus, intended as a means to receive help, hope, and healing [ 49 ]. Pediatric patients with HIV also endorsed feeling God’s presence and being part of a larger force to a greater extent than their HIV-negative counterparts [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, religiosity and spirituality are neither good nor bad per se; rather, it is the way that young patients approach them that might make these two dimensions helpful or detrimental in the context of chronic illness [ 63 ]. Regarding this, the illness narratives of young patients highlighted that, regardless of the type of disorder and religious affiliation, adolescents who placed trust in God, reinforced their relationship with God through prayers or religious services/activities (e.g., reading Holy Scriptures), and saw God as merciful and loving, felt less isolated, and more relieved and comforted, and had a positive outlook on their medical situation [ 42 , 45 , 49 ]. Quantitative studies, similarly, showed that adolescents with chronic illnesses who used positive religious/spiritual coping strategies (e.g., reframing one’s situation from a spiritual perspective) had fewer internalizing and externalizing problems [ 55 ], adhered to medical treatment [ 51 ], and reported better health outcomes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This might have an impact on children's everyday life and in research nowadays involving children with CHD, the focus has changed from survival to how these children experience their everyday life. 5 Earlier studies have shown that they experience physical activities limitation 6,7 and feelings of isolation, 8 but no study has yet studied how children with right ventricle outflow tract anomalies experience their everyday life. To be able to provide support, studies are needed to explore how these children experience the period from assessment to decision, as well as the months thereafter.…”
mentioning
confidence: 99%
“…The religious beliefs of Muslims have a powerful influence on their well-being and attitude in striving to be in good health (Attum & Shamoon, 2018). Previous studies suggested that the sociocultural and religious beliefs can influence how people perceive their illness (Arabiat et al, 2013; Elissa, Bratt, Axelsson, Khatib, & Sparud-Lundin, 2017; Elissa, Sparud-Lundin, Axelsson, Khatib, & Bratt, 2018). For example, social and cultural factors such as stigma impact the daily life of Arab children with T1D (Elissa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%